Increasing Knowledge of Aluminium Craft Entrepreneurs About Digital Marketing to Expand Marketing Reach - Fuad Yanuar Ahmad Rifai; Siswanto Siswanto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
So far, the use of digital marketing by aluminium artisans in Candisari Village, Windusari District, Magelang Regency, has yet to be carried out optimally due to the lack of knowledge of entrepreneurs about digital marketing. Even though entrepreneurs are in areas with internet networks and adequate electronic devices, thus, aluminium artisans can use digital marketing to expand their marketing reach in the hope of increasing their sales. This service specifically aims to 1) Increase partners' knowledge about digital marketing. 2) Partners can take advantage of creating interesting content in digital marketing. This community service will be held in Candisari Village, Windusari District, Magelang Regency. The partners in this dedication are aluminium craftsmen. The service uses the Participatory Action Research (PAR) approach. The digital marketing service activity was attended by 15 partners, all of whom were business actors in the aluminium craft sector. The material presented includes an introduction to digital marketing, social media marketing, e-commerce, digital marketing management, and content marketing. Two resource persons fill digital marketing workshop activities with experience in managing sales using digital technology. This dedication results in the increasing knowledge of partners about digital marketing and how to create interesting marketing content.